2001
DOI: 10.1002/mde.1029
|View full text |Cite
|
Sign up to set email alerts
|

Decision theory and real estate investment: an analysis of the decision‐making processes of real estate investment fund managers

Abstract: Decision theory is the study of models of judgement involved in, and leading to, deliberate and (usually) rational choice. In real estate investment, there are models for the pricing and allocation of assets. These asset allocation models suggest an optimum allocation between the respective asset classes based on retrospective judgements of performance and risk. The representation and role of real estate in a multi-asset portfolio has, historically, been viewed in the context of portfolio theory. Real estate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 9 publications
1
42
1
2
Order By: Relevance
“…The key qualitative overlays identified by the Australian fund managers included judgement ("gut-feeling"), experience and understanding of investing in property assets, feedback from clients or shareholders, fund manager skills, asset quality assessment and peer comparison. The results are comparable to similar studies conducted overseas (French, 2001;Gallimore and Gray, 2002;Worzala and Bajtelsmit, 1997) that identified general experience/intuition, judgement and the use of personal feel of the market, as key qualitative factors that influence institutional property allocation decisions in the USA and the UK. Recent studies by Parker (2011Parker ( , 2013 also identified factors such as judgement, intuition and experience as key qualitative factors that affect property fund manager investment decisions.…”
Section: Factors Influencing Property Allocation Decisionssupporting
confidence: 85%
See 2 more Smart Citations
“…The key qualitative overlays identified by the Australian fund managers included judgement ("gut-feeling"), experience and understanding of investing in property assets, feedback from clients or shareholders, fund manager skills, asset quality assessment and peer comparison. The results are comparable to similar studies conducted overseas (French, 2001;Gallimore and Gray, 2002;Worzala and Bajtelsmit, 1997) that identified general experience/intuition, judgement and the use of personal feel of the market, as key qualitative factors that influence institutional property allocation decisions in the USA and the UK. Recent studies by Parker (2011Parker ( , 2013 also identified factors such as judgement, intuition and experience as key qualitative factors that affect property fund manager investment decisions.…”
Section: Factors Influencing Property Allocation Decisionssupporting
confidence: 85%
“…However, in practice, asset allocation decisions must be made in an environment of incomplete information (particularly physical assets), changing estimates of return, and shifting definitions of the acceptable investment risk. According to French (2001), while definitive inputs to the asset allocation model (historic data or predictive forecasts) are important, fund managers are also influenced by many other non-financial considerations, such as behavioural factors, judgement, intuition and market sentiment (peer group allocation). There is a considerable diversity in the way asset allocations are made, in the use of consultants, in the discretion given to outside managers, and in the way that property investments are managed.…”
Section: Establishing a Quantitative And Qualitative Decision Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…And asset allocation is a powerful tool for risk reduction (Kaplan, 1998). Yet, as the model relies greatly upon historical data as inputs to proffer recommendations on asset allocation and past performance of elements is an important infl uence on the decision (French, 2001), those inputs should be adjusted to refl ect the understanding of the market (Kaplan, 1998). Without such adjustments, the credibility of the analytical result is compromised.…”
Section: Literature Reviewmentioning
confidence: 97%
“…According to Ko and Cheng (2003), fuzzy logic not only provides an approximate but also it is effective descriptions for ill-defined, or troublesome to cope with existing complex systems. The fuzzy approach can capture uncertainty in a realistic way (French, 2001). In order to overwhelm these problems, expert's knowledge is incorporated in modeling.…”
Section: Literature Reviewmentioning
confidence: 99%